Scenariusz filmowy i jego odmiany: Studium przedmiotu. - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Screenplay, Its Kinds and Its Forms Screenplay is a phenomenon located between two different worlds, spheres and cultures: literature and cinema. In his study, Marek Hendrykowski examines the meaning and functions of all crucial terms connected with film script and screenplay, among them: concept, log line, story, synopsis, treatment, draft, first draft, storyboard, director’s draft, final script and shooting script. The author sketches step by step each of these various forms of scenario in detail, explains what they are about and why they are necessary. He also stresses the importance of rewriting and script development in the process of film creation as a means of taking the achievement to a higher level.